Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Isomer effect on energy storage of π-extended S-shaped double[6]heterohelicene - Kumar, Viksit; Bharathkumar, H. J.; Dongre, Sangram D.; Gonnade, Rajesh; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Angewandte chemie-international edition, 2023)
Recently, chiral and nonplanar cutouts of graphene have been the favorites due to their unique optical, electronic, and redox properties and high solubility compared with their planar counterparts. Despite the remarkable progress in helicenes, pi-extended heterohelicenes have not been widely explored. As an anode in a lithium-ion battery, the racemic mixture of pi-extended double heterohelical nanographene containing thienothiophene core exhibited a high lithium storage capability, attaining a specific capacity of 424 mAh g-1 at 0.1 A g-1 with excellent rate capability and superior long-term cycling performance over 6000 cycles with negligible fade. As a first report, the pi-extended helicene isomer (PP and MM), with the more interlayer distance that helps faster diffusion of ions, has exhibited a high capacity of 300 mAh g-1 at 2 A g-1 with long-term cycling performance over 1500 cycles compared to the less performing MP and PM isomer and racemic mixture (150 mAh g-1 at 2 A g-1). As supported by single-crystal X-ray analysis, a unique molecular design of nanographenes with a fixed (helical) molecular geometry, avoiding restacking of the layers, renders better performance as an anode in lithium-ion batteries. Interestingly, the recycled nanographene anode material displayed comparable performance. A pi-extended double heterohelical nanographene of thienothiophene core fused with two hexabenzocoronene units exhibits excellent performance as an anode in a lithium-ion battery. The isomer (PP and MM) with more interlayer distance exhibited a high lithium storage capability compared to the other isomer and racemic mixture. Helical nanographene anodes display excellent rate capability, superior long-term cycling performance, and recyclability.image
Keywords: Battery; graphene; Li-ion battery; nanographene; Organic Electrode Material

Polyvalent interaction and confinement to suppress polysulfide dissolution and improve electrocatalysis - Bharathkumar, H. J.; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Chen, Dehong; Caruso, Rachel A.; Krishnamoorthy, Kothandam (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: cathode material; HIGH-CAPACITY; Particles; SULFUR CATHODE

Effect of imidazolium-based porous polymer binder on the electrochemical performance of lithium sulfur batteries - Senthilkumaran, Marimuthu; Bharathkumar, H. J.; Ramesh, Sivalingam; Basha, K. Anver; Nanaji, Katchala; Babu, Rajendran Prakash (Journal of Power Sources, 2026)
Severe polysulfide shuttle and poor conversion kinetics remain as barriers to make Li-S batteries practically viable. Polymer binders are an important component of a battery electrode although its dosage is very small. Traditionally employed PVDF binder in Li-S batteries has no significant impact in either suppressing the polysulfide shuttle or on their conversion kinetics. Ideally, the binder for a Li-S battery should suppress the polysulfide shuttle, promote the polysulfide conversion and buffer the volume expansion during charge-discharge process. Towards this direction, herein we present a new octyl imidazolium-TFSI based porous polymeric binder (PImz) in combination with CNT/S/Nickel(II) phthalocyanine tetrasulfonic acid tetrasodium salt (Na-NPT) composite. The binder offers strong polysulfide immobilizing capabilities through electrostatic interaction with the imidazolium nitrogen and pore confinement through its porous network, while a small amount of Ni-phthalocyanine could enhance the polysulfide conversion kinetics. Li-S batteries with PImz binder delivered a high specific capacity of 805 mA h/g (0.5 C) with stable performance over 300 cycles. Furthermore, the batteries with high sulfur loading similar to 3 mg/cm(2) delivered a capacity of 820 mA h/g. This newly designed porous polymeric binder is a promising and efficient alternative to the traditionally employed PVDF in terms of synthesis, cost, performance and safety.
Keywords: Imidazolium polymer; lithium sulfur battery; Na-NPT electrocatalyst; polysulfides